2021
DOI: 10.1016/j.abd.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma with compromised margins: retrospective study of management, evolution, and prognosis

Abstract: Background Non-melanoma skin cancer is the most common type of malignancy in the Western world, and surgical excision is the preferred approach. The approach adopted in the face of incomplete excisions of basal cell carcinoma is still controversial. Objectives To compare the number of tumor recurrences after treatment for incompletely excised basal cell carcinoma. Methods Selection and statistical analysis of medical records of patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In terms of the gender distribution of the subjects, depending on the year when the patient was diagnosed with BCC, most of the male subjects were diagnosed in 2019 (39%), and most of the female participants were also diagnosed in 2019 (34%). In their research, Fidelis et al mentioned that that there was a higher incidence of BCC in men than there was in women in Brazil in 2021 [ 17 ]; this is in direct contrast with the higher incidence in men determined by Lang et al [ 18 ]. Miolo et al mentioned that that 218 BCC cases were diagnosed in people who were 66 years of age and older in their study [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…In terms of the gender distribution of the subjects, depending on the year when the patient was diagnosed with BCC, most of the male subjects were diagnosed in 2019 (39%), and most of the female participants were also diagnosed in 2019 (34%). In their research, Fidelis et al mentioned that that there was a higher incidence of BCC in men than there was in women in Brazil in 2021 [ 17 ]; this is in direct contrast with the higher incidence in men determined by Lang et al [ 18 ]. Miolo et al mentioned that that 218 BCC cases were diagnosed in people who were 66 years of age and older in their study [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…In our own study, which exclusively employed standard surgical excisions with serial section histology, the incidence of non-radical operations was notably lower compared to the aforementioned study (16.9%). Nevertheless, it is worth noting that scientific literature suggests that this indicator generally falls within the range of 1 to 40% worldwide [ 19 , 29 , 30 , 31 , 32 ]. To obtain a more precise estimation of the prevalence of incompletely removed tumors, we conducted a literature review.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, a similar trend of statistical dependence was observed, with BCC recurrence after R1 operations being 14.5% higher, while the overall recurrence was 3.2% lower. However, in other studies, this parameter exhibits a wider range of variation (25.0-46.0%) [32]. We also explored publications with lower percentages for the analyzed criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Most BCCs occur on the head and neck (i.e., regions exposed to sun), followed by the trunk and extremities (i.e., relatively unexposed). 3 , 4 Ultraviolet (UV) exposure is the most important carcinogenic factor. 1 Other risk factors include male gender, Fitzpatrick types I and II, a personal history of BCC, chronic arsenic exposure, exposure to ionizing radiation, long-term immunosuppression, genetic syndromes, and family history.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Other risk factors include male gender, Fitzpatrick types I and II, a personal history of BCC, chronic arsenic exposure, exposure to ionizing radiation, long-term immunosuppression, genetic syndromes, and family history. 4 …”
Section: Introductionmentioning
confidence: 99%